Implementation of Internal Control Systems (SPIP) to Strengthen Environmental Health Program Management at Community Health Centers - Fersari, Tika Pustika; Lewis, Maureen; Anell, Anders (Inspektorat Kabupaten Majalengka, 2025)
Effective management of environmental health programs in community health centers (Puskesmas) is crucial to prevent diseases such as acute respiratory infections, diarrhea, and leptospirosis. However, existing practices often rely on reactive rather than preventive risk assessments, limiting program effectiveness. This study investigates the application of the Government Internal Control System (SPIP) in managing environmental health programs, focusing on the mediating roles of transparency and data quality, and the reinforcing role of internal audits. A qualitative descriptive approach was used through interviews with Puskesmas leaders, sanitarians, program staff, and internal auditors, combined with observations and document review. The findings show that transparency in budgeting and program activities, as well as the quality of health data, critically mediate SPIP’s effectiveness, while internal audits remain compliance-oriented. The study contributes conceptually by extending internal control literature to program outcomes and recommends integrating SPIP with transparent, data-driven, and outcome-focused monitoring to strengthen accountability.